Granulocyte colony-stimulating factor and reproductive medicine: A review - Marcelo Borges Cavalcante; Fabrício DA Silva Costa; Ricardo Barini; Edward Araujo Júnior (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Recently, the use of granulocyte colony-stimulating factor (G-CSF) has been proposed to improve pregnancy outcomes in reproductive medicine. Objective: A systematic review of the current use of G-CSF in patients who have difficulty conceiving and maintaining pregnancy was performed. Materials and Methods: Two electronic databases (PubMed/ Medline and Scopus) were searched. Study selection, data extraction and quality assessment were performed in duplicate. The subject codes used were granulocyte colony-stimulating factor, G-CSF, recurrent miscarriage, IVF failure, and endometrium. Results: The search of electronic databases resulted in 215 citations (PubMed/ Medline: 139 and Scopus: 76), of which 38 were present in both databases. Of the remaining 177 publications, seven studies were included in the present review. Conclusion: Treatment with G-CSF is a novel proposal for immune therapy in patients with recurrent miscarriage and implantation failure following cycles of IVF. However, a larger number of well-designed studies are required for this treatment to be established.